Theory-based immunisation health education intervention in improving child immunisation uptake among antenatal mothers attending federal medical centre in Nigeria: a study protocol for a randomized controlled trial - Galadima, Abubakar Nasiru; Mohd Zulkefli, Nor Afiah; Md Said, Salmiah; Ahmad, Norliza; Garba, Saleh Ngaski (Public Library of Science, 2022)
Background: Childhood immunisation coverage is very low in Nigeria (31%) with Zamfara State being amongst the states with the poorest coverage (<10%). Lack of maternal knowledge, attitude, outcome expectations, self-efficacy, cultural beliefs and assumptions of religious regulations of antenatal mothers towards childhood immunisation are the contributory factors to poor childhood immunisation uptake. This study aims is to develop, implement and evaluate the effects of an immunisation health educational intervention with application of Social Cognitive Theory on pregnant women to improve knowledge, attitude, outcome expectations, self-efficacy, cultural beliefs and assumptions on religious regulations regarding childhood immunization uptake in Federal Medical Centre Gusau, Zamfara State, Nigeria. Methodology: The study will be a single-blind parallel-group randomised controlled trial, where baseline data will be collected from 392 estimated antenatal mothers, after that they will be evenly randomised using randomly generated permuted block sizes (each containing two intervention and two control assignments). The study participants will be antenatal mothers of ages 18 years and above who are in third trimesters and attending Federal Medical Centre Gusau, Zamfara State, Nigeria; during the study period and fulfilled all the inclusion and exclusion criteria. The intervention group will undergo five-health education sessions on immunisation, which will be strictly guided by Social Cognitive Theory-based intervention module: while the control group will receive usual care (standard care). Follow-up data will be collected using the same questionnaire at 6-weeks post-delivery, 10-weeks post-delivery and 14-weeks post-delivery. The generalized linear mixed model will be carried-out to determine the overall effect of the intervention after controlling for 14 potential confounding variables. An intention to treat analysis will also be carried-out. Childhood immunisation uptake is the primary outcome while the secondary outcomes are: improved knowledge scores, attitude scores, outcomes expectation, self-efficacy scores, cultural beliefs scores and assumptions on religious regulations scores. Discussion: The study will be a randomised controlled trial, that focuses on the effects of an immunisation health educational intervention with application of Social Cognitive Theory on pregnant women to improve knowledge, attitude, outcome expectations, self-efficacy, cultural beliefs and assumptions on religious regulations regarding childhood immunisation uptake in Federal Medical Centre Gusau, Zamfara State, Nigeria.